Diversity, classification and evolution of CRISPR-Cas systems - Koonin, Eugene V. (Curr Opin Microbiol, 2017)
The bacterial and archaeal CRISPR-Cas systems of adaptive immunity show remarkable diversity of protein composition, effector complex structure, genome locus architecture and mechanisms of adaptation, pre-CRISPR (cr)RNA processing and interference. The CRISPR-Cas systems belong to two classes, with multi-subunit effector complexes in Class 1 and single-protein effector modules in Class 2. Concerted genomic and experimental efforts on comprehensive characterization of Class 2 CRISPR-Cas systems led to the identification of two new types and several subtypes. The newly characterized type VI systems are the first among the CRISPR-Cas variants to exclusively target RNA. Unexpectedly, in some of the class 2 systems, the effector protein is additionally responsible for the pre-crRNA processing. Comparative analysis of the effector complexes indicates that Class 2 systems evolved from mobile genetic elements on multiple, independent occasions.